Analisis Pengaruh Manfaat Dan Keamanan Terhadap Penggunaan Uang Elektronik (Dana) Sebagai Alat Transaksi Pembayaran Dalam Perspektif Ekonomi Islam (Studi Kasus Mahasiswa Ekonomi Islam Angkatan 2019-2021) - Sonia Juatri; Ridhwan Ridhwan; Ary Dean Amri (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2024)
This research is entitled Analysis of the Influence of Benefits and Security on the Use of Electronic Money (Funds) as a Payment Transaction Tool in an Islamic Economic Perspective. This research aims to determine the influence of benefits and security on the use of electronic money (funds) as a means of payment transactions from an Islamic economic perspective. The research method used is quantitative descriptive, with primary data sources. The population used was 314 students from the 2019-2021 Islamic Economics Study Program, Faculty of Economics and Business, Jambi University, and the sample for this research was 76 students taken using proportionate stratifield random sampling. The data analysis techniques used are Partial T test, Simultaneous F test, coefficient of determination, and continued with multiple linear regression analysis. The results of this research show that the Benefit variable has no partial effect and the Security variable has a partial effect on the use of electronic money (DANA) as a means of payment transactions from an Islamic economic perspective. Meanwhile, simultaneously the Benefit and Security variables influence the use of electronic money (DANA) as a means of payment transactions from an Islamic economic perspective.